AKTIVITAS TONIKUM EKSTRAK ETANOL 96% BUNGA KAMBANG PUTIH (Plumeria rubra) PADA MUS MUSCULUS BALB/c - Anna Maria Ulfa; Wahyu Niar Wulan Purnama Sari; Burhanudin Gasim Soka (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Tonic is a preparation used to increase physical strength or stamina. White frangipani (Plumeria rubra) is known to have several potentials such as anti-free radicals, antimicrobials, anti-inflammatory, and contains bioactive compounds such as flavonoids, heterocyclic nitrogen bases, and phenolics. This experiment aims to determine the potential tonic activity of white frangipani flowers extracted with 96% ethyl alcohol on BALB/c musculus and the optimum dose. Tonic activity was evaluated using the natural exhaustion method by measuring the swimming time of mice until exhaustion. The musculus used consisted of 5 groups with 5 replications each, each containing 0.5% sodium carboxymethylcellulose as a negative control, caffeine as a positive control, with variations in doses of 100, 200, and 400mg/kgBW. The results of the treatment showed that the ethanol extract of white frangipani flowers significantly increased the swimming time of mice compared to the negative control. Data processing using one-way ANOVA and subsequent Tukey HSD tests showed a p<0.05 result for the negative control, and differences between treatment groups. The optimal dose was obtained with treatment at 400 mg/kg body weight compared to other doses and was close to the dose in the positive control. The conclusion of this experiment is that frangipani flower extract has potential as a tonic.